Higher governing bodies in besieged Leningrad: sources and digital methods of their analysis - Prigodich, Nikita Dmitrievich (Genesis: исторические исследования, 2025)
The article presents the formulation of the scientific problem regarding the study of actions taken by the higher Soviet and party leadership of Leningrad during the blockade years. The author focuses on the relevance of examining the methods of managing the city under these unique circumstances. The analysis of the distribution of power authority will clarify the principles of Leningrad's functioning during the war and its connection to the overall structure of political leadership in the USSR. In recent years, this area has gained significant momentum due to the publication of a wide range of documents and materials. In this regard, the research's source base consists of a substantial array of decisions and resolutions from the Bureau of the Regional and City Committees of the VKP(b), the Military Council of the Leningrad Front, and the Executive Committee of the Leningrad City Council of Workers' Deputies. The analysis of Soviet-party governance in Leningrad during the Great Patriotic War, based on a large array of decisions and resolutions of power institutions, including appendices and transcripts, relies on methods of historical informatics. The historiographic review of the Soviet and post-Soviet periods allows for conclusions about extensive references made by researchers to the connection between political governance of the city with numerous economic and social themes. However, within this context, there is a palpable lack of attempts to analyze the stated problem using interdisciplinary methods. In this regard, the scientific novelty of the proposed research lies in the approach to the issue at hand. The article provides thematic narratives on the application of historical informatics methods, including computerized content analysis, machine learning, descriptive statistics, and correlation analysis. The capabilities of these methods represent a relevant tool that allows for progress in addressing some of the general tasks posed. Correlating the research results with historiography will yield a more comprehensive understanding of the state management system in besieged Leningrad.